Structural changes in Brazilian employment (2002-2021) - Rodrigo Rodrigues-Silveira (European Commission, Joint Research Centre (JRC), 2023)
The current paper explores the structural changes in employment in Brazil during the period comprehended between 2002 and 2021, subdivided into three sub-periods: 2002-2014, sustained growth and expansion; 2015-2019, political and economic crises; and 2019-2021, the COVID-19 pandemics and its impacts on the labor market. It employs the "jobs approach" (Fernández-Macías 2012; CEA 1996; Wright and Dwyer 2003) to empirically assess the changes during the period considering wage as the fundamental measure of job quality. The Brazilian National Household Survey (PNAD), administered by the IBGE (Brazilian Statistical Office) since 1976, constitutes the core data source. According to the analysis, since the beginning of the 21st century, Brazil has experienced an upgrading in its employment structure. Even considering the macroeconomic and political crises starting in 2015, the advancements observed from 2002 to 2014 were not reverted.
Keywords: 330; Brazilian Labor Market; Structural Change in Employment; Job Quality; Division of Labor